2003
DOI: 10.1177/154405910308200907
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of SaOS-2 Cells Cultured on Different Titanium Surfaces

Abstract: Surface properties may affect the clinical outcome of titanium dental implants. The aim of the present study was to investigate the effects of 3 different titanium surfaces-smooth (S), sandblasted (SB), and titanium plasma-sprayed (TPS)-on proliferation, differentiation, and apoptosis of human osteoblast-like cells, SaOS-2. Cell proliferation was significantly (p < 0.05) higher on the S surface, and synthesis of extracellular matrix proteins was more abundant on TPS and SB than on S surfaces. Analysis of integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 14 publications
(25 reference statements)
5
57
1
4
Order By: Relevance
“…12,14,15,17,19 However, the present in vitro experiment demonstrated that the machined surfaces promoted a favorable cell behavior response, as is also shown in the related literature. 12,14,18,20 Irrespective of the type of surface treatment to which an implant is submitted, in the case of titanium implants, it is their superficial layer of oxide which comes into contact with bone and provides the basis for their exceptional biocompatibility. Moreover, in order for a material to be biocompatible, it must not be cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,14,15,17,19 However, the present in vitro experiment demonstrated that the machined surfaces promoted a favorable cell behavior response, as is also shown in the related literature. 12,14,18,20 Irrespective of the type of surface treatment to which an implant is submitted, in the case of titanium implants, it is their superficial layer of oxide which comes into contact with bone and provides the basis for their exceptional biocompatibility. Moreover, in order for a material to be biocompatible, it must not be cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Some studies have also demonstrated the capacity of machined titanium surfaces to promote cellular adhesion and proliferation. [18][19][20] In addition, rough surfaces enhance osteoblastic phenotype differentiation and the capacity of osteoblasts to synthesize bone matrix. [21][22][23] With regard to cellular morphology related to surfaces with different textures, the related literature has shown that cells spread themselves over a larger area on machined surfaces than they do on rough surfaces.…”
mentioning
confidence: 99%
“…Although this alloy is still widely used in dental and medical fields, some concerns such as toxicity of V and Al and high elastic modulus, have been reported [6][7][8] . Surface roughness and topography can greatly affect the proliferation and protein synthesis of osteoblast cells that are cultured on a metal substrate characteristics in the healing of bone 21,22) . Many studies have demonstrated that roughness has a great influence on cell responses.…”
Section: Surface Characterization and Roughness Testmentioning
confidence: 99%
“…More than macrostructural features, the superficial layer of titanium-oxide and the implant surface microstructure seem to deeply affect bone/fixture interactions [11][12][13] . Many studies 8,10,11,[14][15][16][17][18][19][20][21][22] have shown that a rough surface, when compared to a relatively smooth one, grants better biomolecular adsorption, increases extracellular matrix production and promotes the differentiation of the mesenchymal cells toward an osteoblastic phenotype. Cells may be able to detect variations of the superficial geometry through focal contact mechanisms thus regulating their own phenotypical expression.…”
Section: Introductionmentioning
confidence: 99%